2021
DOI: 10.1111/1477-9552.12427
|View full text |Cite
|
Sign up to set email alerts
|

Crop Choice, Drought and Gender: New Insights from Smallholders’ Response to Weather Shocks in Rural Uganda

Abstract: We analyse gender differences in the response of smallholder farmers to droughts, taking the duration and severity of the event into account. Using a novel weather shock measure that combines spatial rainfall data with detailed cropping calendars, survey data from Uganda and standard econometric techniques, we find that adverse weather events provide an opportunity for women to enter the commercial crop market by allocating land from subsistence to income generating crops. This counterintuitive pattern is, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…Working on one's own arable land is not a priority because the income generated cannot cover household expenses and cannot provide cash in a short time. The same thing was also expressed by Agamile et al [45] when a crisis occurs, the workforce will be diverted to jobs that generate income outside of owned land. For the land itself, women (the housewives) will work on it, such as harvesting coffee, picking up old areca nuts and processing areca nuts, tapping rubber, and other work that requires a minimum amount of labor.…”
Section: Farmer's Adaptation Strategy To Climate Changesupporting
confidence: 53%
“…Working on one's own arable land is not a priority because the income generated cannot cover household expenses and cannot provide cash in a short time. The same thing was also expressed by Agamile et al [45] when a crisis occurs, the workforce will be diverted to jobs that generate income outside of owned land. For the land itself, women (the housewives) will work on it, such as harvesting coffee, picking up old areca nuts and processing areca nuts, tapping rubber, and other work that requires a minimum amount of labor.…”
Section: Farmer's Adaptation Strategy To Climate Changesupporting
confidence: 53%
“…In tropical conditions, rainfall during the growing season was the prime determinant of yield outcomes. A voluminous body of econometric studies has demonstrated that annual or seasonal rainfall variability explains a variety of economic and social outcomes in Uganda (Asiimwe and Mpuga 2007;Björkman-Nyqvist 2013;Agamile, Dimova, and Golan 2021) and in economies with high dependence on rainfed agriculture more generally (Carleton and Hsiang 2016;Dell, Jones, and Olken 2014). The effects of rainfall variability have been found to be most pronounced during extreme events in both directions (droughts or floods), but smaller deviations from the expected rainfall pattern also adversely affect output.…”
Section: Food Yields and Cotton Planting In Ugandamentioning
confidence: 99%
“…These may inform a social understanding of the causes and solutions for drought and may support communities in coping with drought. Further, drought impacts can vary in severity based on gender, ethnic group, religion, livelihood strategies, and other societal roles and vulnerabilities (Agamile et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Most smallholder farmers react to weather shocks by reallocating land to different crops. The situation is particularly difficult for female farmers, for whom the barriers to either adopting shock-mitigating technologies or increasing their off-farm employment are often much higher than for men (Agamile et al, 2021).…”
Section: Introductionmentioning
confidence: 99%